Strategi Manajemen Kurikulum Terintegrasi Layanan Karir - Irwan Maulana; Farhan Ginanjar; Putri Padilah; Siti Nurasiah; Afifah Hijriani (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the integrated curriculum management strategy for career development services in improving student career readiness at Rancamaya Boarding School. The study used a qualitative approach with phenomenological methods through observation, in-depth interviews, and documentation studies. The results indicate that the integration of career services is carried out systematically through the planning, organization, implementation, and evaluation functions of the curriculum. Planning is based on talent and interest mapping, individual counseling, career seminars, campus visits, and partnerships with parents and alumni. The organization demonstrates collaboration between guidance counselors, subject teachers, and school management in developing academic portfolios aligned with student interests. Program implementation is adaptive through flexible counseling services and the integration of academic, extracurricular, and boarding activities. Evaluation is conducted formatively and summatively by the college counseling unit based on data and a three-pillar partnership. Findings indicate that the integrated career services curriculum is able to strengthen students' self-awareness, career exploration, and further study planning.